Dissociable effects of stimulus range on perception and action. (January 2018) - Namdar, Gal; Algom, Daniel; Ganel, Tzvi
Abstract: We have recently reported the discovery that the ability to detect a minimum increment to a stimulus depends on the spread of the other stimuli for which this just noticeable difference (JND) is being measured (Namdar, Ganel, & Algom, 2016). In particular, the JND around a standard stimulus was larger when the other standards tested within the same experimental session spread a larger range. In this study we show that this range of standards effect (RSE) is limited to perceptual estimations and does not extend to action. The JND remained invariant when the participants grasped the objects rather than perceptually estimated their size. This difference supports the hypothesis that visual perception, on the one hand, and visually controlled action, on the other hand, are governed by separate rules and mediated by different mechanisms.